Virtual, Real or Mixed: How Surrounding Objects Influence the Sense of Embodiment in Optical See-Through Experiences? - Genay, Adélaïde; Lécuyer, Anatole; Hachet, Martin (Frontiers in Virtual Reality, 2021)
This paper studies the sense of embodiment of virtual avatars in Mixed Reality (MR) environments visualized with an Optical See-Through display. We investigated whether the content of the surrounding environment could impact the user’s perception of their avatar, when embodied from a first-person perspective. To do so, we conducted a user study comparing the sense of embodiment toward virtual robot hands in three environment contexts which included progressive quantities of virtual content: real content only, mixed virtual/real content, and virtual content only. Taken together, our results suggest that users tend to accept virtual hands as their own more easily when the environment contains both virtual and real objects (mixed context), allowing them to better merge the two “worlds”. We discuss these results and raise research questions for future work to consider.